ТРИФЕНИЛФОСФИН БРОМИДЛИ КОМПЛЕКС ТУЗ СИНТЕЗИ (Scientific journal of the Fergana State University, 2023)
This article affirms that one of the main factors for increasing the yield of fruit trees is their protection from pests and diseases. In recent years, plant protection has paid great attention to the use of harmless biological control methods for the environment, humans and animals. An example is the use of the use of pheromones, which can be separated from different insects. Practical significance is the production and use in practice of pheromones of insect pests by chemical methods, which adversely affect the plant world.